ANALYSIS OF BREACH OF CONTRACT IN SHOPHOUSE LEASE AGREEMENTS IN THE COMMERCIAL DISTRICT - Putri, Deviana; Asyari, Fatimah; Farahwati; Pasaribu, Benhard Kurniawan (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
This study aims to analyze the forms of default that occur in shop house lease agreements in the commercial area of Samarinda City and to examine the mechanisms for resolving them. The background of this study is based on the fact that the commercial area in Samarinda is growing rapidly, making shop rental practices an important necessity for economic activities. However, on the other hand, these practices are prone to disputes due to the failure of one party to fulfill their obligations. This study uses an empirical method, where data is obtained through interviews and the distribution of questionnaires to 25 respondents (shop owners and tenants), as well as case documentation at the Samarinda District Court. The results of the study show that the most dominant form of default is late payment of rent, experienced by 62% of shop owners, followed by misuse of shop functions at 18%, and unilateral termination of contracts at 12%. In terms of dispute resolution, 70% of cases were resolved non-judicially through deliberation and mediation, while 30% resolved through litigation in court. The study also found that most lease agreements were made without the involvement of a notary or legal advisor, so that the clauses of the agreement tended to be simple and legally weak. Thus, this study concludes that default in shop lease agreements in Samarinda City is a real and recurring problem, but it can still be minimized through stronger agreements, the involvement of notaries, and increased legal awareness among the parties. This study is expected to contribute to the development of civil law, particularly in the practice of lease agreements in commercial areas.